PENERAPAN METODE PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKANMOTIVASI BELAJAR SISWA PADA MATA DIKLAT PELAYANAN PRIMADI KELAS X-PM 2 SMKN 2 BLITAR - PERMATA INDI, AGNEL (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
This study describes the research on the implementation method of Role Playing on the subject service excellence-in-class Marketing X SMK Negeri 2 Blitar with a purpose to find out the motivation for learning of students following the application of role playing teaching method. The author uses class-action research design (CAR). CAR is used on the implementation of the research activities at the time of learning. CAR consists of four stages, namely, planning, action, observation, and reflection. The research was taken in accordance with the research objectives are to enhance students ‘ motivation for learning. From the results of research conducted, teachers ‘ observations showed an average score of 3.10 meaning both in the implementation of learning. For the observation of student learning activities 3 implementation means effective learning. For student motivation for learning from the results of questionnaires that were distributed in every round, from 36 students 28% answered strongly agree, agree, answer 59% 13% answered don’t agree, while to answer strongly disagree there is no student who answered. Keywords: CAR, Role Playing Learning Method, Learning Motivation.